Review paper: Organ transplants: ethical, social, and religious issues in a multicultural society - Robson, N.Z.M.H.; Razack, A.H.; Dublin, N. (SAGE Publications, 2010)
Recent advances in the fields of organ donation and organ transplant have introduced new hope for the treatment of serious diseases. However, this promise has been accompanied by several issues. The most common issue raised is ethical implications, but in a multicultural society like Malaysia, additional concerns arise pertaining to social and religious issues. These concerns needs to be addressed as attitudes toward and acceptability of organ donation varies according to social, culture, and religion. The diverse cultural, religious, and traditional concepts pertaining to organ donation may hamper its acceptability and cause a lack of willingness to donate organs. The purpose of this article is to briefly explore the ethical issues involved in organ transplant and the various religious opinions on organ donation. It is hoped that this knowledge and understanding may benefit both health care providers and patients in a multicultural society like Malaysia.